PHONETIC EXPRESSIVE MEANS: ALLITERATION, ONOMATOPOEIA - Axmadjonova Oydinoy; G’ofurova S. M. (TADQIQOTLAR, 2026)
Abstract: This article examines the role of phonetic expressive means, particularly alliteration and onomatopoeia, in the stylistic organization of language and literary texts. Phonetic devices function as important tools that enhance the emotional, aesthetic, and imaginative qualities of speech through the deliberate arrangement of sounds. The article focuses on the linguistic nature of alliteration as the repetition of similar consonant sounds in neighboring words, which contributes to rhythm, musicality, and emphasis within a text. It also analyzes onomatopoeia as the imitation of natural or environmental sounds through language, allowing writers to create vivid auditory imagery and intensify the sensory perception of the reader. Special attention is given to the stylistic functions of these phonetic expressive means in literary discourse, where they help to convey mood, strengthen semantic content, and produce a stronger emotional impact. The study demonstrates that alliteration and onomatopoeia are not merely decorative elements of language but significant stylistic devices that enrich the expressive potential of speech and contribute to the artistic effectiveness of literary works.